Primary Norfloxacin Prophylaxis for APASL-Defined Acute-on-Chronic Liver Failure: A Placebo-Controlled Double-Blind Randomized Trial. (17th April 2022) - Kulkarni, Anand V.; Tirumalle, Sowmya; Premkumar, Madhumita; Kumar, Karan; Fatima, Syeda; Rapole, Bindu; Simhadri, Venu; Gora, Baqar Ali; Sasikala, Mitnala; Gujjarlapudi, Deepika; Yelamanchili, Sadhana; Sharma, Mithun; et al.
Abstract : INTRODUCTION: This study aimed to evaluate the role of prophylactic norfloxacin in preventing bacterial infections and its effect on transplant-free survival (TFS) in patients with acute-on-chronic liver failure (ACLF) identified by the Asian Pacific Association for the Study of the Liver criteria. METHODS: Patients with ACLF included in the study were randomly assigned to receive oral norfloxacin 400 mg or matched placebo once daily for 30 days. The incidence of bacterial infections at days 30 and 90 was the primary outcome, whereas TFS at days 30 and 90 was the secondary outcome. RESULTS: A total of 143 patients were included (72 in the norfloxacin and 71 in the placebo groups). Baseline demographics, biochemical variables, and severity scores were similar between the 2 groups. On Kaplan-Meier analysis, the incidence of bacterial infections at day 30 was 18.1% (95% confidence interval [CI], 10–28.9) and 33.8% (95% CI, 23–46) ( P = 0.03); and the incidence of bacterial infections at day 90 was 46% (95% CI, 34–58) and 62% (95% CI, 49.67–73.23) in the norfloxacin and placebo groups, respectively ( P = 0.02). On Kaplan-Meier analysis, TFS at day 30 was 77.8% (95% CI, 66.43–86.73) and 64.8% (95% CI, 52.54–75.75) in the norfloxacin and placebo groups, respectively ( P = 0.084). Similarly, TFS at day 90 was 58.3% (95% CI, 46.11–69.84) and 43.7% (95% CI, 31.91–55.95), respectively ( P = 0.058). Thirty percent of infections were caused by multidrug-resistant organisms. More patients developed concomitant candiduria in the norfloxacin group (25%) than in the placebo group (2.63%). DISCUSSION: Primary norfloxacin prophylaxis effectively prevents bacterial infections in patients with ACLF. Abstract :